Inspired, magical, connected: How virtual reality can make you well - Quesnel, Denise (The Conversation, 2017)
Research shows that virtual reality experiences can help social disconnection and improve wellness - by inspiring awe.
Keywords: Riecke_2017; denise-quesnel; dissemination-4generalPublic; mediaCoverage